Effect of tree size attributes on fruit production and animal-mediated seed dispersal web in Melia azedarach L. (Chinaberry) in north-west Himalaya, India - Sukumaran Arun; Sasidharan Sarath; Khanduri Vinod Prasad; Suraj; Rawat Shweta; Chand Vaisakhy Prem (Folia Oecologica)
Insights into the relationships between tree species and their potential seed dispersers in a specific region are vital for determining spatial distribution and population dynamics that rely solely on natural regeneration. Several factors influence fruit production in trees, and the fluctuations in fruit output directly affects the population and diversity of frugivores in that area. We examined the trees of Melia azedarach to analyse the impact of tree size attributes (diameter, height and crown length) on fruit yield. Furthermore, we observed the seed dispersers to determine their role in fruit removal and dispersal. The average fruit production among sample trees varied from 1.8 × 103 to 1.18 × 105. Out of the 10 bird species recorded, the Hypsipetes leucocephalus (Himalayan Black Bulbul) and Pycnonotus leucogenys (Himalayan Bulbul) were the most frequent visitors and crucial for seed dispersal of M. azedarach. Psittacula krameri (Rose-ringed Parakeets) dropped a significant quantity of fruits below the parent tree, acting as a pre-dispersal seed predator. There were significant variations among species in total visits and estimated endocarp disbursed. Our findings indicate that the tree-size attributes like diameter, height, and crown length strongly affected fruit yield capacity in trees of Melia azedarach. Large trees are likely to be reproductively matured and are prioritising resources for reproduction rather than growth. Native animals, especially birds are facilitating seed dispersal in M. azedarach. The estimated period of the availability of ripe fruits reflects the status of seed predators and seed dispersal. The results ultimately revealed that the animal plant interactions of this study would be vital for ecosystem functioning, habitat rewilding and conservation of the ecosystem through balancing plant-animal mutualism.